(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
This article focuses on the role of the management function of motivation in ensuring the effective functioning of the educational services market, the management functions in higher education to maintain internal stability, its integrity and structure, as well as to choose a strategy for the development of its activity, and to prepare and implement suitable recommendations for working in a competitive environment.